GIS AND HYDRODYNAMIC MODELING TO ANALYZE THE POTENTIAL OF FLASHFLOOD HAZARDS IN BT. KURANJI SUB-WATERSHED, WEST SUMATRA - Deni Sabriyati; M. Pramono Hadi (Yayasan Citra Dharma Cindekia, 2021)
Flash flood disaster has caused casualties and property losses due to excess rainfall which is rapidly occurred in a relatively short period. To analyze the potential of flash flood hazards in Bt. Kuranji Sub-watershed, West Sumatra Province, this study was conducted with hydrodynamic modeling using GIS which is consist of three analyses: (1) hydrological analyses such as the analyzes of peak-discharge, SCS-CN, and SCS Unit Hydrograph using HEC-HMS software ; (2) hydraulics analyses comprised of morphometry analyzes and flood modeling using HEC-RAS software; (3) the analyzes hazard potentials obtained from the depth and the velocity of the hydraulic analyzes result. Hydrological analyzes were performed in return periods of 2, 5, 10, 20, 50, and 100 years using 38 years of rain data which, the greatest flood potential is in the 100-year return period with Tp 3 hours and peak discharge 725 m3/s. The magnitude of flash flood discharge is the input data on the hydraulics analyses that found the area, velocity, depth, and flood water level. From the hydraulic analyses, flash floods during the 100-year period are known to have the potential to hit 20 urban villages with the high level of hazard is 8.36%, the moderate level is 52.76%, and the low level is 38.88%.